Historical roots of the Old Testament (1200-63 BCE) - Nelson, Richard D. (Richard Donald), 1945- (Biblische Enzyklopädie., 2014)
"A thorough overview of the history of ancient Israel for research and classroom use Richard D. Nelson charts the beginning of the Iron Age and the emergence of Israel and its literature, including the kingdoms of Israel and Judah, the downfall of Israel, Judah in the Assyrian and Babylonian periods, Yehud and Persia, and the Hellenistic period. Each chapter provides a summary of the period under consideration, a historical reconstruction of the period, based on biblical and extrabiblical evidence; a critical study of the biblical literature deriving from or associated with the period, and theological conclusions that readers may draw from the relevant biblical texts. Features: Balanced coverage of controversial topics Extensive bibliographies at the beginning of each chapter Lists of rulers and key dates for reference and classroom use"--EBSCO